(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper is an analysis of what the impact of GST (Goods and Services Tax) is on Indian Tax Scenario. Here stated with a brief description of the historical scenario of Indian taxation and its tax structure. Then the need arose for the change in tax structure from traditional to GST model. GST has be detailed discuss in this paper as the background, silent features and the impact of GST in the present tax scenario in India. The Goods and Services Tax (GST) is a value added tax to be implemented in India. GST is the only indirect tax that directly affects all sectors and sections of our economy. Ignorance of law is no excuse but is liable to panel provisions, hence why not start learning GST and avoid the cost of ignorance. Therefore, we all need to learn it whether willingly or as compulsion. The goods and services tax (GST) is aimed at creating a single, unified market that will benefit both corporate and the economy. The changed indirect tax system GST-Goods and service tax is planned to execute in India. Several countries implemented this tax system followed by France, the first country introduced GST. Goods and service tax is a new story of VAT which gives a widespread setoff for input tax credit and subsuming many indirect taxes from state and national level. The GST is declared by government on 01 April 2017. India is a centralized democratic and therefore the GST is implemented parallel by the central and state governments as CGST and SGST respectively. The objective will be to maintain a commonality between the basic structure and design of the CGST, SGST and SGST between states .In this article, I have started with the introduction, in general of GST and have tried to highlight the objectives the proposed GST is trying to achieve. Thereafter, I have discussed the possible challenges and threats and then, opportunities that GST brings before us to strengthen our free market economy.